A review on therapeutical potential of paeonol in atherosclerosis - Yu, Wei; Ilyas, Iqra; Aktar, Nasrin; Xu, Suowen (Frontiers in Pharmacology, 2022)
The morbidity and mortality of atherosclerotic cardiovascular disease (ASCVD) is increasing year by year. Cortex Moutan is a traditional Chinese medicinal herb that has been widely used for thousands of years to treat a wide variety of diseases in Eastern countries due to its heat-clearing and detoxifying effects. Paeonol is a bioactive monomer extracted from Cortex Moutan, which has anti-atherosclerotic effects. In this article, we reviewed the pharmacological effects of paeonol against experimental atherosclerosis, as well as its protective effects on vascular endothelial cells, smooth muscle cells, macrophages, platelets, and other important cell types. The pleiotropic effects of paeonol in atherosclerosis suggest that it can be a promising therapeutic agent for atherosclerosis and its complications. Large-scale randomized clinical trials are warranted to elucidate whether paeonol are effective in patients with ASCVD.